Systematic review on physical exercise interventions in patients with burnout syndrome - Rosales Ricardo, Y.; Pedro Ferreira, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Burnout Syndrome (SB) is a mental health problem with a high social impact. The objective was to synthesize evidence from studies on the effectiveness of physical exercise interventions in patients with burnout syndrome through a systematic review. This was done by reviewing articles published in databases: Pubmed, Web of Science, Scielo, ScienceDirect and PsycoINFO. As search terms: exercise, physical activity, burnout. In Spanish, English and Portuguese. We found 4768 studies that were first reduced to 13 studies with an average of 64.0 %, following the TREND method. In most of the studies patients in the intervention groups with different physical exercises had a greater reduction in their SB levels than those who did not receive intervention.